Epidemiology of pancreatic cancer in France: descriptive study from the French national hospital database. Issue 8 (August 2017) - Maire, Frédérique; Cibot, Jean-Olivier; Compagne, Catherine; Hentic, Olivia; Hammel, Pascal; Muller, Nelly; Ponsot, Philippe; Levy, Philippe; Ruszniewski, Philippe
Abstract : Introduction: Although indirect evidence suggests that the incidence of pancreatic adenocarcinoma has increased in the last decade, few data are available in European countries. The aim of the present study was to update the epidemiology of pancreatic cancer in France in 2014 from the French national hospital database (Programme de Médicalisation des Systèmes d'Information). Patients and methods: All patients hospitalized for pancreatic cancer in France in 2014 in public or private institutions were included. Patient and stays (length, type of support, institutions) characteristics were studied. The results were compared with those observed in 2010. Results: A total of 13 346 (52% men, median age 71 years) new patients were treated for pancreatic cancer in 2014, accounting for a 12.5% increase compared with 2010. Overall, 22% of patients were operated on. Liver metastases were present in 60% of cases. The disease accounted for 146 680 hospital stays (+24.8% compared with 2010), 76% of which were related to chemotherapy (+32%). The average annual number and length of stay were 7 and 2.6 days, respectively. In 2014, 11 052 deaths were reported (+15.8%). Conclusion: Approximately 13 350 new cases of pancreatic cancer were observed in France in 2014. The increase in incidence was associated with a marked increase in hospital stays for chemotherapy.